PHYSICOCHEMICAL STANDARDIZATION OF KUSHTA ABRAK SAFAID: A HERBO-MINERAL UNANI FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Abrak (Mica) is a rock forming silicate of aluminium and is used in Unani system in the form of kushta (calcined product). After proper purification and incineration abrak becomes highly potent and is used in treatment of various diseases of respiratory system, stomach and intestine, tuberculosis, asthma, spermatorrhoea etc. Hakim describes abrak as antipyretic, general tonic, aphrodisiac, constipative and desiccant. Product standardization of a compound formulation is utmost necessary to check the purity and genuineness of a preparation. In this study the purification, preparation and standardization of kushta abrak safaid was performed. Kushta was evaluated on classical parameters like finger test, fineness test etc. as well as on modern parameters like bulk density, tapped density, hausner’s ratio, carr’s index, pH, loss of weight on drying, total ash, acid insoluble ash, water soluble ash, extractive value and loss of weight on ignition. The physicochemical parameters evaluated in this study might be considered as standard parameters of kushta abrak safaid.